2020
DOI: 10.1126/sciadv.aax1425
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid quantum memory–enabled network at room temperature

Abstract: Teaser: Building quantum network with roomtemperature atomic and all-optical memories for scalable quantum information processing.Quantum memory capable of storage and retrieval of flying photons on demand is crucial for developing quantum information technologies. However, the devices needed for long-distance links are quite different from those envisioned for local processing. Here, we present the first hybrid quantum memory enabled network by demonstrating the interconnection and simultaneous operation of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Various physical systems 8 such as atomic ensembles 2,4,9 and single quantum systems, including single atoms 10,11 , ions 12,13 and solid-state spins 14,15 have been proposed as nodes. The atomic-ensemble-based nodes, which were initially proposed in the Duan-Lukin-Cirac-Zoller (DLCZ) protocol 4 , are formed by quantum interface (QIs) that create quantum correlations between a spin wave (SW) and a photon via spontaneous Raman emissions (SREs) induced by a write pulse 2,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] . The quantum correlations created via SREs form the basis of generating entanglement between a photonic qubit and a SW qubit 2,[30][31][32][33] .…”
mentioning
confidence: 99%
“…Various physical systems 8 such as atomic ensembles 2,4,9 and single quantum systems, including single atoms 10,11 , ions 12,13 and solid-state spins 14,15 have been proposed as nodes. The atomic-ensemble-based nodes, which were initially proposed in the Duan-Lukin-Cirac-Zoller (DLCZ) protocol 4 , are formed by quantum interface (QIs) that create quantum correlations between a spin wave (SW) and a photon via spontaneous Raman emissions (SREs) induced by a write pulse 2,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] . The quantum correlations created via SREs form the basis of generating entanglement between a photonic qubit and a SW qubit 2,[30][31][32][33] .…”
mentioning
confidence: 99%
“…Except for utilizing all matter-based quantum memory as quantum node, all-optical quantum memory can also act as quantum node. In 2020, X. L. Pang et al demonstrated room-temperature connection between atomic ensembles and an all-optical loop memory [228] by sending a write-out photon from the atoms to the optical loop memory.…”
Section: Quantum Network With Other Physical Systems and Hybrid Appro...mentioning
confidence: 99%
“…When it comes to quantum storage time, the main challenge with room-temperature atomic ensembles is their thermal motion and/or collisional decoherence. Due to those limitations the DLCZ-type single-photon sources in room-temperature vapors have been up to now limited in their on-demand retrieval time to a few microseconds 22 24 . Another limitation on the performance of DLCZ-type sources has been the quantum readout noise 25 .…”
Section: Introductionmentioning
confidence: 99%